If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -3) + -6x = 8 Reorder the terms: 4(-3 + x) + -6x = 8 (-3 * 4 + x * 4) + -6x = 8 (-12 + 4x) + -6x = 8 Combine like terms: 4x + -6x = -2x -12 + -2x = 8 Solving -12 + -2x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -2x = 8 + 12 Combine like terms: -12 + 12 = 0 0 + -2x = 8 + 12 -2x = 8 + 12 Combine like terms: 8 + 12 = 20 -2x = 20 Divide each side by '-2'. x = -10 Simplifying x = -10
| 5(-6z+20)=-18z-19-5z | | 300x+400=250x+300 | | 5(-6z+20)=-18z-19-5z | | 300x+400=250x+300 | | f(5c)=10c-4 | | y=x(squared)+6x+25 | | 5(-6z+20)=-18z-19-5z | | -3(r-4)+7=-15 | | C=3.55+0.25x | | Y-.75=500 | | gd+1=15-d | | 2x-9x+8=-6 | | (2X+27)+(2X-11)=100 | | x^4+2x^3-1024=0 | | -5.1n-3.94=14.98-4n | | Y-.6Y=140 | | (x+4)squared-25=0 | | 72-50y^2=0 | | y=25x+175 | | 72+2v^2= | | 2/9=k+3/2 | | 10+0.25x=20 | | (x+4)-25=0 | | -0.48+8.2c=-0.5c-2+8.6c | | -47=-3x-8 | | 4k+8k=2(10+8k)-12(k-9) | | 8x^4-11x^2+1=0 | | 4+3(c-12)= | | .8888x=-16 | | .8888x=-16 | | 72u^2+24uv+2v^2= | | 72u^2+24uv+2v^2= |